P187 Keeping children safe from medication harm: the MEDSIQ journey. (June 2019) - Roueché, Alice; Runnacles, Jane; Muszynska, Kasia
Abstract : Background: In 2015 the UK Royal College of Paediatrics and Child Health (RCPCH) launched www.medsiq.org, an innovative website for sharing resources and quality improvement projects relating to paediatric medication safety. MedsIQ was founded in response to increasing awareness that children and young people are frequently harmed by errors in their medication. Children are 3 times more likely than adults to be harmed by medication errors and it has been shown that up to 15% of inpatient prescriptions have errors on them (1). What is MedsIQ?: Medication safety is a complex issue and innovative approaches to combat the problem are needed. Part of the answer lies with the medical community; most clinical teams have tried to tackle the problem; by auditing prescribing standards or having pharmacists on ward rounds, through to more innovative drug calculator apps, e-prescribing tools and Druggles (a safety huddle focusing on medication errors). The MedsIQ platform has been developed to allow people to share their ideas. Submitted projects and resources are peer-reviewed and shared online. Alongside the website, there is a Champions' Network – a community of practice in improving paediatric medication safety, who participate in webinars and face-to-face events to enable deeper discussion of shared challenges and solutions. Impact: Since launching in 2015 the website has had more than 70 resources, over 1100 registered users and a growing community of Champions. To maintain the wider network there are bi-monthly webinars to discuss diverse medication safety topics. These webinars have raised safety issues that have gone on to shape national strategy via the RCPCH. They are accessed frequently on YouTube. There have been a series of well-attended MedsIQ events hosted at the RCPCH to bring clinicians, families and researchers together to discuss medication safety. Through these events MedsIQ has been able to work closely with families and the public to support safe administration of medicines within the community. Where next?: In direct response to topics raised at MedsIQ events and webinars, the MedsIQ team are working closely with their partners, Wellchild and Medicines for Children, to help develop a new app to support families to manage medications in the home environment. This app is due to launch in March 2019. Following the success of MedsIQ, the RCPCH is launching QI central, a website that extends the MedsIQ concept to all areas of paediatric Quality Improvement. This website launches in March 2019.